The Control System Of School Operational Assistance Funds (BOS) From The Perspective Of Good Governance - Fanisa Nahla; Baiq Anggun Hilendri Lestari (Cita konsultindo, 2025)
This study aims to analyze the management of the School Operational Assistance Fund (BOS) at Sekolah Dasar Negeri 5 Ampenan, with a focus on the application of the principles of good governance. This research explores how the principles of flexibility, effectiveness and efficiency, accountability, and transparency are implemented in the management of BOS funds. In addition, it also identified challenges faced in the supervision of BOS funds, including a lack of coordination between institutions and unclear procedures. Constraints related to the reporting and disbursement of BOS funds were also a concern in this study. The research method used was qualitative with data collection techniques through interviews, observation, and documentation. The results showed that in general, the principles of good governance have been well implemented in the management of BOS funds at SD Negeri 5 Ampenan. Nevertheless, challenges in supervision and obstacles in reporting and disbursing BOS funds still need to be overcome. Overall, the management of BOS funds at SD Negeri 5 Ampenan contributed positively to the improvement of school quality, especially in terms of fulfilling operational needs and improving the quality of learning.